MacAddict Making Music with GARAGEBAND - Shaffer, Jay; Rosenzweig, Gary (Que, 2004)
Do you find yourself singing in the shower, pretending your shampoo bottle is your microphone and your towel is your guitar? Do you tap out drum rhythms with your pen at work? Now you can channel your musical energy using The MacAddict Guide to Making Music with GarageBand, the Mac software program that can turn you into a virtual recording star. MacAddict's focused, no-olds-barred approach is evident in this musical tutorial. Learn about pre-recorded loops that enable you to sound like you're singing with a symphony orchestra even if you can't actually play a single instrument. Or, if you are instrumentally-inclined, you will also learn how to hook up your instruments to record your own sound and later use GarageBand to edit and mix it for truly professional results. MacAddict is the authoritative voice in the Mac community and The MacAddict Guide to Making Music with GarageBand is the only book they endorse. It is sure to become the only book you'll need to learn how to unleash your inner rock star.